2022
DOI: 10.1590/1984-0462/2022/40/2021172in
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection in children and adolescents: a Brazilian experience

Abstract: Objective: To describe clinical and epidemiological aspects of children and adolescents infected with the SARS-CoV-2 in the Municipality of Taubaté, SP, from March to November 2020. Methods: Cross-sectional study with secondary data obtained from the Epidemiological Surveillance System about confirmed cases in city residents and from medical records of patients who were treated in hospitals in Taubaté, aged between 0 and 19 years. Chi-square and Student’s t tests were used for comparisons. Results: 677 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The pediatric age group with SARS-CoV-2 presents individuality in its clinical characteristics, which seems to evade the notorious severity of adult and elderly patients [ 14 , 15 ]. In children and adolescents, a milder pattern of COVID-19 is observed, with few reports of severity when compared the adult population [ 16 ]. We identified that all the studied range is susceptible to COVID-19, but it was most observed in adolescents (45/34.9%), followed by children from 1 year to 5 years (39/30.2%) and then newborns (26/20.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric age group with SARS-CoV-2 presents individuality in its clinical characteristics, which seems to evade the notorious severity of adult and elderly patients [ 14 , 15 ]. In children and adolescents, a milder pattern of COVID-19 is observed, with few reports of severity when compared the adult population [ 16 ]. We identified that all the studied range is susceptible to COVID-19, but it was most observed in adolescents (45/34.9%), followed by children from 1 year to 5 years (39/30.2%) and then newborns (26/20.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that high transmissibility can result from diagnostic failures, possibly explained by the occurrence of mild symptoms or even the absence of symptoms in this age group, thus maintaining the spread of the disease. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Obviamente, no início da pandemia, ou no início de qualquer outra doença infecciosa, não há estudos completos, clínica e experimentalmente bem controlados, que forneçam evidências sólidas para responderem a esta complexa e importante questão. Todavia, em função da continuidade do surto pandêmico em vários países do globo, pesquisadores sistematicamente foram revelando evidências acerca da associação entre transmissão do vírus e de sua letalidade em crianças, e adultos, comparando ambientes escolásticos e não escolásticos (Santos et al, 2021).…”
Section: Crianças E Disseminação Do Vírus Da Covid-19unclassified